Letter - Schevenels, Walther, b. 1894
012a-0030-001 INTERNATIONAL FEDERATION OF TRADE UNIONS 9, AVENUE D'ORSAY, PARIS-VIIe Sch/H TELEGRAMS INTERFED- PARIS TELEPHONE INVALIDES 45-88 EXECUTIVE COMMITTEE : President W. M Citrine. Great Britain Vice-Presidents: H. Jacobsen, Denmark ; L. Jouhaux. France; E Kupers. Holland: Corn. Mertens, Belgium : R Tayerle, Czechoslovakia General Secretary : W Schevenels AFFILIATED COUNTRIES ARGENTINE AUSTRIA BELGIUM CANADA CZECHOSLOVAKIA DANTZIG DENMARK DUTCH EAST INDIES ESTONIA FRANCE GREAT BRITAIN GREECE HOLLAND HUNGARY INDIA LUXEMBURG MEMEL TERRITORY MEXICO NORWAY PALESTINE POLAND ROUMANIA SOUTH AFRICA SOUTH-WEST AFRICA SPAIN SWEDEN SWITZERLAND YUGOSLAVIA Letter F.I de Sol No. 1053 7th November 1938. Mr. H. Tewson London Dear Comrade Tewson, I thank you for your letter of the 4th November, regarding proposals for Spain, in connection with which I had this morning a conversation with Comrade Jouhaux, who is in full agreement with proposals (1) and ( 2), i.e., that an international campaign for Spain should be decided on by the forthcoming General Council meeting. As you know, the question of whether the campaign for Spain is still to be organised in conjunction with the LSI is one to be considered at the same special General Council meeting, to be held on the 9th and 10th November. With regard to the second point in your letter, Jouhaux agrees to approach the French Government for the removal of the ban on arms, so that each of the British and French Movements will be supported in its representations to its respective government by the simultaneous action being taken in the other country, which will serve as an additional argument. Points (3), (4) and (5), which you merely included for the sake of order, have been carefully noted. Yours sincerely, W. Schevenels, General Secretary 292/946/12a/30